Antimalarial activity and phitochemical analysis from Suruhan (Peperomia pellucida) extract - Nurhayati Bialangi; Moh Adam Mustapa; Yuszda K Salimi; Ari Widiantoro; Boima Situmeang (Pascasarjana Universitas Negeri Medan, 2016)
Abstract. Infectious and parasitic diseases is one of various disease that the most common. Based on data from the World Health Organization (WHO) in 2011, infectious and parasitic diseases become the third largest cause of death in the world. One of the plants that have potential as an antimalarial is suruhan (Peperomia pellucida). The purpose of this study is to test antimalarial activity against Plasmodium falciparum and analysis photochemistry consituen from extract suruhan. Antimalarial activity test using Desjardin method. Extraction was done by using maceration wuth methanol as a solvent and fractionation using partition methods. Results of phytochemical screening revealed the presence of alkaloids, flavonoid, steroid, saponins and triterpenoid test results antimalarial activity fraction of n-hexane, ethyl acetate and water show IC50 values are 12.80, 2.90 and 10.74 mg/ mL respectively.Keyword: Peperomia pellucida, suruhan, antimalarial